Looking back on Partition. Issue 3 (3rd July 2018) - Butalia, Urvashi
Abstract : Seventy years after the partitioning of India into two countries, India and Pakistan, the bitter legacies of that violent founding moment have not gone away. While explorations based on oral histories had begun to open up Partition histories, there is still a great deal to be done and the need to record the stories of survivors is urgent as more and more of them are dying out. But even as direct histories become more diffuse and elusive, other explorations have begun to open up as research moves into the hands of non academics, writers, theatre activists and others.